Determinant Variables Affecting Accounting Conservatism (In Consumer Goods Sector Manufacturing Companies Listed On The Indonesia Stock Exchange In 2020-2022) - Venus Fernando Firdaus; Yosandy Yulius; Dwi Eriyanto; Abdullah Muksin (Journal of Accounting and Finance Management, 2023)
The purpose of this study is to determine the effect of company growth, investment opportunity set, and debt covenant variables on accounting conservatism. This study used a sample of 60 respondent data consisting of 20 (twenty) companies with the consumer good sector listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. Sampling using purposive sampling technique and using the explanatory method. Collecting data in this study used a document review technique, where data collection was carried out by reviewing the related company's financial statements. descriptive statistical analysis, by carrying out the coefficient of determination, multiple regression analysis, and hypothesis testing. The research was conducted using the Eviews program version 12. The results show that: 1) Company Growth has no partial effect on Accounting Conservatism; 2) Investment Opportunity Set partially has no effect on Accounting Conservatism; 3) Debt Covenant partially has a positive and significant influence on Accounting Conservatism; and 4) Debt Covenant, Investment Opportunity Set, and Debt Covenant have a significant influence on Accounting Conservatism. According to the coefficient of determination test, which finds an R Square value of 0.731617 or 73.16%, the independent variables in this study are able to explain the dependent variable of 73.16%. This shows that Company Growth, Investment Opportunity Set, Debt Covenant together (simultaneously) have a significant effect on accounting conservatism.